APPROACHES TO THE STATISTICAL ANALYSIS OF INVESTMENT IN HUMAN CAPITAL IN UKRAINE - SIRENKO, KATERYNA; MAZUR, MARHARYTA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article analyzes the development of the investment process in human capital in Ukraine. The approaches to the statistical analysis of investment in human capital in the country are considered in the article. Ukraine has low indicators of human capital development, including demographic characteristics and living standards indicators. The development of human capital is an actual task of economic development policy of the state. Therefore, the issue of statistical analysis and determination of prospects for the development of investment in human capital in Ukraine requires additional research. During the last years the position of Ukraine according to the international human development index is improving constantly. Despite the fact that the country has satisfied levels of education and life expectancy components of the index, but low values of gross national product per capita negatively influence on the growth of economic development of the country. Besides, the country’s population is steadily declining and is accompanied by rising mortality rates and declining in birth rates as well as the migration of working-age population. The approaches to determining the amount of investment in human capital, in particular in health care, education, physical development, social protection and social security have been also analyzed. It is established that investing in human capital development is not reflected in the growth of living standards and increase in demographic indicators in the country. The tendencies and prospects of human capital development in Ukraine are studied. The results of the study allow not only to assess the values and dynamics of investment in human capital, but also to identify conditions that constrain their growth, and to suggest directions for further ways to expand them.